Functional Ionic Liquids Decorated Carbon Hybrid Nanomaterials for the Electrochemical Biosensors - Pushpesh Ranjan (MDPI AG, 2021)
Ionic liquids are gaining high attention due to their extremely unique physiochemical properties and are being utilized in numerous applications in the field of electrochemistry and bio-nanotechnology. The excellent ionic conductivity and the wide electrochemical window open a new avenue in the construction of electrochemical devices. On the other hand, carbon nanomaterials, such as graphene (GR), graphene oxide (GO), carbon dots (CDs), and carbon nanotubes (CNTs), are highly utilized in electrochemical applications. Since they have a large surface area, high conductivity, stability, and functionality, they are promising in biosensor applications. Nevertheless, the combination of ionic liquids (ILs) and carbon nanomaterials (CNMs) results in the functional ILs-CNMs hybrid nanocomposites with considerably improved surface chemistry and electrochemical properties. Moreover, the high functionality and biocompatibility of ILs favor the high loading of biomolecules on the electrode surface. They extremely enhance the sensitivity of the biosensor that reaches the ability of ultra-low detection limit. This review aims to provide the studies of the synthesis, properties, and bonding of functional ILs-CNMs. Further, their electrochemical sensors and biosensor applications for the detection of numerous analytes are also discussed.